A therapeutic trial of decitabine and vorinostat in combination with chemotherapy for relapsed/refractory acute lymphoblastic leukemia. Issue 9 (27th June 2014) - Burke, Michael J.; Lamba, Jatinder K.; Pounds, Stanley; Cao, Xueyuan; Ghodke‐Puranik, Yogita; Lindgren, Bruce R.; Weigel, Brenda J.; Verneris, Michael R.; Miller, Jeffrey S.
<x xml:space="preserve">Abstract</x> DNA hypermethylation and histone deacetylation are pathways of leukemia resistance. We investigated the tolerability and efficacy of decitabine and vorinostat plus chemotherapy in relapse/refractory acute lymphoblastic leukemia (ALL). Decitabine (15 mg/m2 iv) and vorinostat (230 mg/m2 PO div BID) were given days 1–4 followed by vincristine, prednisone, PEG‐asparaginase, and doxorubicin. Genome wide methylation profiles were performed in 8 matched patient bone marrow (BM) samples taken at day 0 and day 5 (postdecitabine). The median age was 16 (range, 3–54) years. All patients had a prior BM relapse, with five relapsing after allogeneic transplant. The most common nonhematological toxicities possibly related to decitabine or vorinostat were infection with neutropenia (grade 3; n = 4) and fever/neutropenia (grade 3, n = 4; grade 4, n = 1). Of the 13 eligible patients, four achieved complete remission without platelet recovery (CRp), two partial response (PR), one stable disease (SD), one progressive disease (PD), two deaths on study and three patients who did not have end of therapy disease evaluations for an overall response rate of 46.2% (CRp + PR). Following decitabine, significant genome‐wide hypo‐methylation was observed. Comparison of clinical responders with nonresponders identified methylation profiles of clinical and biological relevance. Decitabine and vorinostat followed by re‐Induction chemotherapy was tolerable and demonstrated clinical benefit in relapsed patients with ALL. Methylation differences were identified between responders and nonresponders indicating interpatient variation, which could impact clinical outcome. This study was registered at www.clinicaltrials.gov as NCT00882206. Am. J. Hematol. 89:889–895, 2014. © 2014 Wiley Periodicals, Inc.